Pemenuhan Hak-Hak Anak Pasca Kelahiran dalam Perspektif Islam: Strategi Membangun Keluarga Sejahtera di Era Kontemporer - Herlina, Herlina; Rahmah, Fadila; Efendy, Asip; Adib, Muhammad; Erlina, Erlina; Hijriyah, Umi (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2024)
Children's rights apply from birth, even while they are still in the womb, and parents and society are responsible for fulfilling them. The family is an important place that shapes a child's morals and character. The purpose of this research is to enhance our understanding of the role of the family in facing the challenges of globalization and how Islamic-based parenting is very important. This research uses a descriptive qualitative approach, namely a literature review. Formulating research objectives, defining key concepts, determining the unit of analysis, and searching for relevant data are all data collection techniques. The primary data comes from written sources related to the research. And the final step, drawing conclusions from the research findings. This research found that children's rights are a gift from God, which include the rights to religion, identity, health, education, and protection from threats. The implementation of children's rights today faces issues such as exploitation, limited education, mental health problems, etc. Families, communities, and the government must work together to create an environment that supports children's rights and well-being. There is a possibility that the character education provided by the family is responsible for the formation of the child's morals. Parents, religious values, and social environment also play a role in helping children behave positively in facing today's challenges.